2016
DOI: 10.1016/j.envpol.2016.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Deep challenges for China's war on water pollution

Abstract: China's Central government has released an ambitious plan to tackle the nation's water pollution crisis. However, this is inhibited by a lack of data, particularly for groundwater. We compiled and analyzed water quality classification data from publicly available government sources, further revealing the scale and extent of the crisis. We also compiled nitrate data in shallow and deep groundwater from a range of literature sources, covering 52 of China's groundwater systems; the most comprehensive national-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(125 citation statements)
references
References 25 publications
1
104
0
4
Order By: Relevance
“…China is undergoing rapid economic development that has led to severe environmental pollution including groundwater quality deterioration (Han et al 2016). Two papers in this special issue are from Chinese scholars and relate to this concern.…”
Section: Manuscripts Selected For the Special Issuementioning
confidence: 99%
“…China is undergoing rapid economic development that has led to severe environmental pollution including groundwater quality deterioration (Han et al 2016). Two papers in this special issue are from Chinese scholars and relate to this concern.…”
Section: Manuscripts Selected For the Special Issuementioning
confidence: 99%
“…Thus, the coastal area had the potential for substantial pollution reductions. Additionally, Han et al [14] reported that the river water in the eastern regions was highly polluted, which provided an incentive for local governments to better manage their wastewater. In contrast, a low pollution intensity was observed in the western provinces in 2004, and they therefore had less potential for additional emission reductions [15].…”
Section: Industrial Wastewater Management Policies and Trends In Chinamentioning
confidence: 99%
“…The surface water quality is graded on six-grade scale. 30 The following table shows the surface water quality standards in China.…”
Section: Water Pollution Caused By Municipal Industries and Agriculturementioning
confidence: 99%